KADAR TOTAL FLAVONOID DAN FENOL PADA BUNGA DAN BUAH KARAMUNTING (Melastoma malabathricum) - Aina Dwi Qulfi (Universitas Lambung Mangkurat, 2026)
Karamunting (Melastoma malabathricum) is a wild shrub that is widely found on the mainland of Kalimantan, especially South Kalimantan. Karamunting is widely used by the community as food and traditional medicines. The potential of karamunting needs to be researched so that it can be utilized more optimally. This study aims to measure and compare the difference in the levels of phenol and flavonoid compounds in karamunting fruits and flowers. Simplicia extraction uses the maceration method with ethyl acetate solution. The measurement of flavonoid and phenol levels was using the UV-Vis Spectrophotometry method with a standard solution of quercetin for flavonoid compounds, and a standard solution of galic acid for phenolic compounds. The analysis of research data used the SPSS application with the T Test between flower organs and fruit organs. The results of the study found that the total level of flavonoids in flower ethyl acetate extract (17,940 ± 0.26 mg QE/g) was higher than the flavonoid level in fruit ethyl acetate extract (7,307 ± 0.11 mg QE/g). The phenol content in the flower ethyl acetate extract (398.148 ± 0.75 mg GAE/g) was higher than the phenol content in the fruit ethyl acetate extract (260.370 ± 0.26 mg GAE/g). The total levels of flavonoids and phenols in the ethyl acetate extract of karamunting flowers were significantly different from the total levels of flavonoids and phenols in the ethyl acetate extract of karamunting fruit.